Empowering Diversity in Education: A Web-Based Tool for Real-Time Sign Language Detection - Meda, Shefqet; Leka, Oresti; Kamberaj, Hiqmet (European Scientific Journal, ESJ, 2024)
This study aims to give an overview of the disabilities faced by people around the world and, in particular, in Albania. It also highlights the primary concern of the deaf community, such as the expression. This study presents a solution to this problem through a real-time sign language detection web application. First, the structural and functional aspects of the application are described by the standard software specification requirements. Then, a description of the software architecture follows. The technological aspect of the application is entirely defined by expressing all the significant implementations of each programming language contained behind the software diagrams and architecture. The main goal is to provide the latest technologies in the market combined with a well-planned and developed image detection application that is scalable, portable, maintainable, and efficient in Empowering Diversity in Education. This technologically up-to-date application is delivered as a full-stack web application. The application produces results that waver between 85%-95% quality off detection; it consists of a bi-partite backend, one for creating and compiling models, namely Python, TensorFlow, and Jupyter Notebooks, and the other part held by Node.JS to power the front-end built with React and TensorFlow’s JS. This study presents a fully developed web-based application that has the potential to impact and improve diversity in education significantly